Discussion on the development of offshore floating photovoltaic plants, emphasizing marine environmental protection - Wu, Sheng; Jiang, Nian; Zhang, Shuai; Zhang, Pingping; Zhao, Peng; Liu, Yang; Wang, Yanhui (Frontiers in Marine Science, 2024)
The development of solar energy is one of the most effective means to deal with the environmental and energy crisis. The floating photovoltaic (PV) system is an attractive type because of its multiple advantages and has been well developed based on fresh water areas on land. This paper focuses on the expansion of this sector towards the ocean, offshore floating PV plants, which is the new growth point with huge potential for the future PV sector. For this new field, the technology readiness level is really low and research to understand the interaction between offshore floating PV plants and marine environment are proceeding. In this paper, we aim to discuss the technological feasibility of offshore floating PV plants as well as analyze potential impacts on the marine environment during the life cycle of PV from manufacturing until disposal.